Peran Gereja Terhadap Pencegahan Perilaku Kekerasan Dalam Rumah Tangga: Sudut Pandang Teologis - Sinurat, Hersakso; Nainggolan, Justinos Ray; Alexander, Irving Josafat (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
This study examines the role of the church in addressing Domestic Violence (DV) behavior from a theological perspective. DV encompasses physical, sexual, psychological abuse, and neglect within the household, which often occurs in Christian families where women frequently become victims. Although DV cases continue to increase, the church’s role in addressing this issue remains limited. This study employs a literature review method to analyze Biblical perspectives and various research findings on the church’s role in addressing DV. The findings indicate that DV constitutes a violation of human rights and individual dignity, contrary to Christian teachings on love, respect, and responsibility. The church plays a crucial role in providing moral support and counseling for families facing DV. The church can take proactive steps through premarital counseling, marriage counseling, and family recovery seminars to prevent and address DV within the Christian community, underscoring the importance of protection for victims and church support in the recovery process for families affected by DV.